Principles guiding ethical research in a collaboration to strengthen Indigenous primary healthcare in Australia: learning from experience. Issue 1 (13th January 2021) - Bailie, Jodie; Laycock, Alison Frances; Conte, Kathleen Parker; Matthews, Veronica; Peiris, David; Bailie, Ross Stewart; Abimbola, Seye; Passey, Megan Elizabeth; Cunningham, Frances Clare; Harkin, Kerryn; Bainbridge, Roxanne Gwendalyn
Abstract : Introduction: Indigenous communities worldwide are leading calls for all research involving Indigenous people to be underpinned by values and principles articulated by them. Many researchers are explicitly adopting these principles to guide what, where, how and when research is undertaken with Indigenous people. With critical reflection to support the implementation of such principles largely absent from published literature, this paper explores both the implementation of, and the outcomes from a set of guiding principles used in a large-scale Australian research collaboration to improve Indigenous health. Methods: In this inductive qualitative study, we adopted a principles-focused evaluation approach. Based on interviews with 35 actors in the collaboration and a review of project documents, we generated themes that were then iteratively discussed, refined and categorised into (1) 'strategies'—activities by which implementation of our guiding principles were recognised; (2) 'outcomes'—results seen from implementing the principles and (3) 'conditions'—aspects of the context that facilitated and constrained implementation of the principles. Results: Respondents found it difficult to articulate how the guiding principles were actually implemented, and frequently referred to them as part of the fabric of the collaboration. They viewed the set of principles as mutually reinforcing, and as providing a rudder for navigating complexity and conflict. Implementation of the principles occurred through five strategies—honouring the principles; being dynamic and adaptable; sharing and dispersing leadership; collaborating purposefully and adopting a culture of mutual learning. Outcomes included increased Indigenous leadership and participation; the ability to attract principled and values-driven researchers and stakeholders, and the development of trusting and respectful relationships. The conditions that facilitated the implementation of the principles were collaborating over time; an increasing number of Indigenous researchers and taking an 'innovation platform' approach. Conclusion: Our findings show that principles guiding collaborations are valuable in providing a focus, direction and a way of working together when they are collaboratively developed, hold genuine meaning for all members and are implemented within a culture of continuous critical reflection, learning and adaptation, with ongoing reinterpretation of the principles over time.